Decolonising Pedagogies: Unpacking Postcolonial Language Policies in Higher Education Systems of South Africa and Zimbabwe - Taringa, Beatrice; Manyike, Tintswalo Vivian (Forum for Linguistic Studies, 2024)
Following their independence from colonial rule, most African nations adopted postcolonial language policies. As a result, some southern African countries were held accountable for implementing an exoglossic policy that favoured foreign colonial languages; in contrast, other independent states took an exclusive stance that gave preference to native tongues in their socio-economic sectors. This article therefore sought to evaluate the accomplishments made in the last three to four decades since South Africa and Zimbabwe became democratic republics. The article is timely, as we are drawing closer to the mid-target of the Decade of Mother Tongue 2022-2032 proclaimed by UNESCO, an organisation that is also the custodian of the fund for the cause. Cultural capital theory was chosen as the theoretical framework for this investigation. The theory revealed how language education policy frameworks and regulations affect the way indigenous languages are taught and learned in the curriculum of the two countries. The nature of this investigation was qualitative, as it used a multiple case study approach, employing two examples of language in education policies in Zimbabwe and South Africa respectively. A reportable narrative about accomplishments to date was woven together based on thematic web-like data analysis. Discourse analysis was done on national language policy frameworks and language education policies germane to the teaching and learning of indigenous languages. The results show that the milestones achieved included the inclusion of indigenous languages in the national constitutions of both countries, the design of language education policies and the elevation of indigenous languages to languages of teaching and learning in institutions of higher education and schools, languages of communication in governance, the establishment of language institutes, training teachers for language and making corpus planning and digitising indigenous languages. Based on these findings, the study therefore recommends similar studies in other contexts.